2010
DOI: 10.1001/archophthalmol.2010.255
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Proliferative Retinopathy in a Brazilian Population of Preterm Infants With the Screening Algorithm WINROP

Abstract: To retrospectively validate the WINROP (weight, insulinlike growth factor I, neonatal, retinopathy of prematurity [ROP]) algorithm in a Brazilian population. WINROP aims to predict ROP and is based on longitudinal weight measurements from birth until postmenstrual age 36 weeks. WINROP has predicted 100% of severe ROP in 3 neonatal intensive care unit settings in the United States and Sweden. Methods: In children admitted to the neonatal intensive care unit at Hospital de Clínicas de Porto Alegre, Porto Alegre,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
55
3
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(66 citation statements)
references
References 23 publications
4
55
3
3
Order By: Relevance
“…This could explain the higher ROP incidence rate found. 15 The Cryotherapy for Retinopathy of Prematurity (CRYO-ROP) study showed an incidence of 65.8%. 16 However, the weight criterion required for inclusion in the study was lower than that of the present study (weight < 1,250 grams).…”
Section: Discussionmentioning
confidence: 99%
“…This could explain the higher ROP incidence rate found. 15 The Cryotherapy for Retinopathy of Prematurity (CRYO-ROP) study showed an incidence of 65.8%. 16 However, the weight criterion required for inclusion in the study was lower than that of the present study (weight < 1,250 grams).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, clinical prediction models to early identify patients in risk of ROP were presented. WINROP [29][30][31] and PINT-ROP 32 were presented using postnatal longitudinal weight gain measurements. ROPScore, by the other hand, uses the BW and the weight measured at completed 6 weeks of life as weighted values in the final calculation of the score.…”
Section: Discussionmentioning
confidence: 99%
“…So far, our results are in accordance with the results from Sweden and USA reporting 100% sensitivity (and therefore, by induction, 100% negative predictive values) (ref. 26,32,33,[38][39] ) while studies from China, Mexico, Brazil or Korea [34][35][36][37] reported sensitivity values ranging from 85% to 95%. The WinROP system correctly identified all 24 infants requiring or potentially requiring treatment (Type 1 or Type 2).…”
Section: Discussionmentioning
confidence: 99%
“…Based on the results of weekly weight increments in Swedish infants, an online system WinROP was created aiming at timely prediction of a high risk of serious ROP development 25,32,33 . Several studies that evaluated ROP in different populations have been published with varying results 23,25,26,[32][33][34][35][36][37][38][39] . In this paper, we would like to contribute to this discussion by presenting an evaluation of the WinROP system based on data acquired at our department.…”
Section: Introductionmentioning
confidence: 99%